2010
DOI: 10.1177/104063871002200617
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Necropsy-Associated Coagulase-Positive Staphylococci in Horses

Abstract: Abstract. Coagulase-positive staphylococci (CoPS) are potential causative agents of equine infections, but they are rarely responsible for the death of the animal. In the current study, staphylococci implicated in the death or euthanasia of horses were retrospectively studied in 3,457 necropsies performed over a decade (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006). Morbidity associated with CoPS was 1.7%, representing 60 isolates of CoPS, which were identified as Staphylococcus aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…ST8-type MRSA has also been recently isolated in Australian horses [15]. In France, only one molecular study has been performed on MRSA isolated in horses [10]. In this study, only three MRSA were identified among 59 S. aureus equine isolates and all belonged to the ST8 [10].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…ST8-type MRSA has also been recently isolated in Australian horses [15]. In France, only one molecular study has been performed on MRSA isolated in horses [10]. In this study, only three MRSA were identified among 59 S. aureus equine isolates and all belonged to the ST8 [10].…”
Section: Discussionmentioning
confidence: 96%
“…In France, only one molecular study has been performed on MRSA isolated in horses [10]. In this study, only three MRSA were identified among 59 S. aureus equine isolates and all belonged to the ST8 [10]. ST398-type MRSA is a non-CC8 clone initially report in France in pigs [6], which is currently spreading in horse clinics in Europe and North America [10, 12, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Veterinary Medicine the resistance to glycopeptides has been hardly studied due to little use. According to Haenni et al (2010) Aminoglycoside class showed one of the best level of susceptibility in this study, ranging from 7.69% to 25.81%, as well as phenicols.…”
Section: Discussionmentioning
confidence: 99%
“…In several cases, patients that contracted an infection caused by S . pseudintermedius , in particular newborn puppies, have died or been euthanized due to the lack of effective treatment to remedy the medical condition [4, 7, 8]. Thus there is a critical need for the discovery and characterization of novel antimicrobials to treat infections caused by methicillin-sensitive and methicillin-resistant S .…”
Section: Introductionmentioning
confidence: 99%